2022
DOI: 10.1016/j.scog.2021.100235
|View full text |Cite
|
Sign up to set email alerts
|

Latent inhibition, aberrant salience, and schizotypy traits in cannabis users

Abstract: Aberrant salience processing may underlie the link between cannabis and psychosis, as posited in individuals with schizophrenia or high schizotypy. We investigated the relative effects of cannabis use, schizotypy status, and self-reported aberrant salience experiences on salience processing, measured using a latent inhibition (LI) task (Granger et al., 2016), in a non-clinical population. A university sample of 346 participants completed the Schizotypal Personality Questionnaire (SPQ), Aberrant Sali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…This set of personality traits can range from minimal disturbances to psychotic disorders in the general human population [ 140 ]. A number of studies have shown that latent inhibition can also be impaired in this disorder [ 141 , 142 ], which allows us to consider the behavioral phenotype of rats after US PS also as a model, reproducing schizotypy symptoms, that may have important practical relevance as schizotypy allows us to explore the etiological pathways underlying schizophrenic spectrum psychopathology [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…This set of personality traits can range from minimal disturbances to psychotic disorders in the general human population [ 140 ]. A number of studies have shown that latent inhibition can also be impaired in this disorder [ 141 , 142 ], which allows us to consider the behavioral phenotype of rats after US PS also as a model, reproducing schizotypy symptoms, that may have important practical relevance as schizotypy allows us to explore the etiological pathways underlying schizophrenic spectrum psychopathology [ 139 ].…”
Section: Discussionmentioning
confidence: 99%
“…Latent inhibition has been demonstrated in a variety of species; as already noted, it has been observed in goats and sheep (Lubow & Moore, 1959), but it has also been demonstrated in rats (Kaye & Pearce, 1987), in pigeons (Tranberg & Rilling, 1978), honeybees (Abramson & Bitterman, 1986), and even snails (Loy et al, 2006). While latent inhibition can also be found in humans (e.g., Dawes et al, 2022; Evans et al, 2007; Granger et al, 2016), there has been sustained debate about the extent to which the effect is demonstrable without embedding the exposure within other so-called “masking” tasks (for a review, see Byrom et al, 2018). In addition, there is some suggestion that latent inhibition has a peculiar developmental trajectory, in that it is seemingly evident in younger children, but not older children.…”
mentioning
confidence: 99%
“…However, there are sufficient nuances and shortcomings within the study of the development of latent inhibition to warrant further investigation. In the current study, we employed a task used on several occasions to successfully reveal an effect of stimulus preexposure on later learning in young adults (Dawes et al, 2022; Granger et al, 2016). During the preexposure stage of this task, participants are repeatedly presented with a series of individual letters (D, M, T, or V) which are presented on screen for 1,000 ms and separated by an interstimulus interval of 50 ms.…”
mentioning
confidence: 99%